Demonstration Method to Improve Prayer Practice - Suhulah, Ghina Agniya; Tabroni, Imam; Jiao , Deng; Guilin , Xie (Journal Emerging Technologies in Education, 2023)
Background. In the process of learning fiqh at MDA Ar-Rahmah, a variety of learning methods are needed and in accordance with the subject matter to be taught by the teacher. Purpose. One of the learning methods is using the demonstration method. Method. Various methods or techniques of presenting subject matter can be utilized by teachers in teaching and learning activities. Results. In this study, researchers used the Classroom Action Research method (action research). So that this research procedure is adjusted to the Classroom Action Research (PTK) procedure which is carried out in a cyclic process, where each cycle consists of three meetings with four phases, including: (1) planning, (2) action implementation, (3) observation, and (4) reflection. Conclusion. Based on the results of the study that children's abilities after using the demonstration method at MDA Ar-Rahmah have increased which can be seen in each Cycle I and II, where in cycle I there were 7 children categorized as not yet developing (46%), 8 children categorized as starting to develop (53%) and in cycle II there were 15 children categorized as starting to develop (100%) and cycle III there were 10 children starting to develop (67%) and 5 children categorized as developing as expected (33%).